Athabasca River (Alice B. Donahue Library & Archives)
View from the Grand Rapids overlooking the West Channel on the Athabasca River, Alberta. Left to right is Kim LeMessurier (nee Chamberlain), Ralph Johnson, Real Boisvert. Boisvert, Real; LeMessurier; Johnson, Ralph photograph